An Analysis of Marketing Mix At Nafira Batik Sumedang - Shofia Anisa Ratnasari; Wartini Yulianti (Journal of Bussines Management Basic, 2023)
The focus of this research is to analyze the marketing mix at Nafira Batik Sumedang. Thisstudy aims to determine the implementation of the current marketing mix and the obstacles and solutions to Nafira Batik Sumedang. The method used in this research is a qualitative research method and the sampling technique used is purposive sampling. Meanehile, in analyzing the data, the Miles and Huberman model was used with the following steps : data collection, data reduction, data presentation and conclusions, the way to test the validity was by using triangulation techniques. Researchers focus on the implementation of the marketing mix on products and promotions with the indicators used are product mix width, product mix length, product mix depth, product mix consistency, advertising, personal selling, public relations, sales promotion, and direct marketing. The results show that the marketing mix at Nafira Batik Sumedang has been implemented well but has not been maximized due to changes in customer tastes and weak digital marketing and sales promotions that are not carriedout intensely. With efforts to conduct market research again and innovative products aswell as improve the procurement of competent and skilled human resources